Pengaruh Rasio Hutang Jangka Panjang, Hutang Jangka Pendek, Dan Ekuitas Terhadap Profitabilitas Perusahaan-Perusahaan Sektor Consumer Goods Di Bursa Efek Indonesia (2005-2009) - , Wiwit Nurwidya Hening ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study investigates the influence of long-term debt ratio, short-term debt ratio, and equity ratio on profitability of consumer goods firms in Indonesian Stock Exchange. There are 29 sample of consumer goods firms in this study. The study used secondary data from 2005 to 2009 collected from the selected Annual Report. The Annual Report published by the Indonesian Capital Market Directory (ICMD) and Indonesian Stock Exchange. Pooled Ordinary Least Squares (OLS) model, Fixed Effect Model (FEM), dan Random Effect Model were used in the analysis. The result indicate that longterm debt and short-term debt ratio significantly influence on profitability. Although the impact of equity ratio on the profitability is not significant. Longterm debt and short-term debt ratio are positively correlated with profitability. The result also suggest that Fixed Effect Model (FEM) is the best model used in the study. The result suggest that consumer goods firms in Indonesia depend on external financing Â±50%, and the others used equity. In consumer goods firms in Indonesia case, a high proportion of debt is represented in short-term debt (Â±30%). The study suggest that companies should implement effective and efficient credit policy, which will improve the performance and growth. Finally, the top management should take interest the issue of capital structure and constantly monitor situation in their companies.